Anomalous superficial peroneal nerve and variant cutaneous innervation of the sural nerve on the dorsum of the foot: a case report - Nagabhooshana, Somayaji (BioMed Central, 2009)
BACKGROUND: The superficial peroneal nerve is a branch of common peroneal nerve. There are reports about the variant course and distribution of this nerve. The sural nerve arises from the tibial nerve in the popliteal fossa. The variations of the above nerves described here are unique and provide significant information to surgeons dissecting lower limb. CASE PRESENTATION: The present case is about some important anatomic variations observed in left lower limb of approximately 55 - year - old male cadaver. The variations were; high division of superficial peroneal nerve into medial and lateral branches, lateral branch descending in the anterior intermuscular septum in a peroneal tunnel before piercing the deep fascia and variant distribution of sural nerve on the dorsum of the foot. The probable clinical significances of the variation are discussed. CONCLUSION: Awareness of anatomical variations of superficial peroneal and sural nerves such as those presented here becomes important to avoid injury in real clinical situations.